2018
DOI: 10.1101/lm.046359.117
|View full text |Cite
|
Sign up to set email alerts
|

Prepared stimuli enhance aversive learning without weakening the impact of verbal instructions

Abstract: Fear-relevant stimuli such as snakes and spiders are thought to capture attention due to evolutionary significance. Classical conditioning experiments indicate that these stimuli accelerate learning, while instructed extinction experiments suggest they may be less responsive to instructions. We manipulated stimulus type during instructed aversive reversal learning and used quantitative modeling to simultaneously test both hypotheses. Skin conductance reversed immediately upon instruction in both groups. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…5, 6) and the aversive domain (Figs. 7-9), corresponding to what has been reported for adult flies (Tully and Quinn 1985;Tully et al 1990;Ren et al 2012;Wu et al 2012;Chouhan et al 2015), bees (Giurfa 2003;Mota and Giurfa 2010;Pérez Claudio et al 2018), and vertebrates (Rajalakshmi and Jeeves 1965;O'Malley and Bruning 1969;Morris and Dolan 2004;Bissonette et al 2008;Costa et al 2015;Izquierdo et al 2017;Atlas and Phelps 2018). This suggests reversal learning as a general faculty widespread in the animal kingdom, even where the nervous system is numerically as simple as is the case for the larva with its ∼10,000 neurons (Dumstrei et al 2003;Nassif et al 2003).…”
Section: Generality Of Reversal Learning Across Valence Domainssupporting
confidence: 66%
“…5, 6) and the aversive domain (Figs. 7-9), corresponding to what has been reported for adult flies (Tully and Quinn 1985;Tully et al 1990;Ren et al 2012;Wu et al 2012;Chouhan et al 2015), bees (Giurfa 2003;Mota and Giurfa 2010;Pérez Claudio et al 2018), and vertebrates (Rajalakshmi and Jeeves 1965;O'Malley and Bruning 1969;Morris and Dolan 2004;Bissonette et al 2008;Costa et al 2015;Izquierdo et al 2017;Atlas and Phelps 2018). This suggests reversal learning as a general faculty widespread in the animal kingdom, even where the nervous system is numerically as simple as is the case for the larva with its ∼10,000 neurons (Dumstrei et al 2003;Nassif et al 2003).…”
Section: Generality Of Reversal Learning Across Valence Domainssupporting
confidence: 66%
“…The subtle change in the learning context might explain this effect because-in contrast to the day before -no explicit instructions about the contingencies were given. Previous studies have demonstrated that explicit contingency reversal instructions are capable of reversing conditioned responses as measured by SCR [31][32][33][34] , startle reflex 35 , and verbal evaluations 36 . Although contingency reversal was not explicitly modeled, the lack of instruction might have resulted in an ambiguous state of US uncertainty followed by increased physiological responses to both CS+ and CS−.…”
Section: Discussionmentioning
confidence: 99%
“…Here, participants are informed after a differential conditioning phase that the contingencies from the previous phase will be reversed in the subsequent phase. Research using this procedure has demonstrated that these instructions successfully reversed conditioned SCRs with neutral CSs (Grings et al, 1973;Wilson, 1968) and fear-relevant CSs (i.e., pictures of snakes and spiders) (Atlas & Phelps, 2018;McNally, 1981). Mertens and De Houwer (2016a) have recently extended these studies by demonstrating that also conditioned potentiated startle reflexes can be reversed with contingency reversal instructions.…”
Section: Contingency Reversal Instructionsmentioning
confidence: 99%
“…Nevertheless, the results of these studies are not uncontested. That is, other studies have demonstrated that verbal instructions can moderate conditioned fear installed via CS-US pairings to fear-relevant CSs as well (Atlas & Phelps, 2018;McNally, 1981;McNally & Foa, 1986; for a review of these studies see McNally, 1987). Likewise, several studies have demonstrated that verbal instructions can abolish differential startle responses established through CS-US pairings (Luck & Lipp, 2015a;2015b;Mertens & De Houwer, 2016a).…”
Section: Integration With Mental Process Models Of Fear Learningmentioning
confidence: 99%